The Tradition of Reading Five Selected Surahs After Fardu Prayer: Study Living Qur’an at Pondok Pesantren Al-Qur’an Asy-Syahadah Surabaya - Mahdalina Nanda Alhusna; Muhammad Muslich Aljabbar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
This article examines The Living Qur’an phenomenon at the Pondok Pesantren Al-Qur’an Asy-Syahadah Surabaya, which has been taking place since 2018 and is carried out through the tradition of reciting five selected surahs after the obligatory prayers. The surahs recited include al-Fīl, al-Inshirāh, al-Nasr, al-Falaq, and al-Mu’minūn [23]: 29. This phenomenon reflects a routine practice that is consistently carried out, thereby fostering a spiritual culture within the boarding school environment. This research is important because it demonstrates how the Qur’anic text is alive in the daily reality of the pesantren through deeply rooted collective practices. The objective of this study is to describe the process of carrying out the tradition and to understand its meaning for the caretakers, administrators, and students. The method used is qualitative, specifically field research. The Living Qur’an approach is combined with Karl Mannheim’s Sociology of Knowledge analytical framework. Data sources were obtained through observation, interviews, documentation, and supporting literature. The research findings indicate that the tradition of reciting five selected surahs is performed in congregation and in sequence according to specific protocols. Surah al-Fīl is recited seven times, al-Inshirāh once with certain phrases repeated in both surahs al-Nasr once, al-Falaq three times, and al-Mu’minūn [23]:29 eleven times. From the perspective of Karl Mannheim’s Sociology of Knowledge, the meaning of this tradition encompasses three dimensions: objective meaning as an obligatory practice; expressive meaning as a form of worship, self-protection, and inner peace; and documentary meaning as a collective culture deeply rooted in the lives of the students.